Human-made sounds in informal learning spaces on a university campus - Zhang, Jia; Ding, Ding; Chen, Jiachao; Liu, Chunlu; Luther, Mark; Zhao, Jilong; Liu, Changan (International Journal of Strategic Property Management, 2024)
The university property management department has been facing a challenge with the strategic management of campus spaces due to the need for informal learning spaces (ILSs) to facilitate students’ independent studies. However, there’s limited research on how these ILSs perform, particularly concerning human-made sounds. This study delves into the impact of human-made sounds on students, considering their individual differences and positive experiences in various types of ILSs within an Australian university campus. The investigation includes open-ended questions to delve deeper into students’ positive experiences with human-made sounds across different ILSs. The research findings demonstrate that the impact of human-made sounds on students is influenced by certain individual characteristics. Additionally, the study identifies three types of positive experiences regarding human-made sounds in ILSs for students: a sense of relaxation induced by human-made sounds, the sound-masking effect, and increased motivation for learning. This study could assist university property managers in understanding students’ perceptions of human-made sounds and aid in strategic management of campus space that aligns with students’ needs and preferences for ILSs, improving the overall learning environment and support student success.